The Political Culture of Asian Brazilians - Benjamin Zhu; Lucas Toshiaki Archangelo Okado; Ednaldo Aparecido Ribeiro (Política & Sociedade, 2022)
Few studies have examined the relationship between race and politics for Asian Brazilians. Using data from the Latin American Public Opinion Survey, we examine this relationship along two axes: cognitive orientation towards politics and institutional confidence. We use factor analysis to create representative indices of these axes and estimate regression models using race as a predictive variable. We find no evidence that Asian Brazilians differ from White Brazilians along either of these two axes. However, we find that a university education has an especially strong relationship with cognitive orientation towards politics for Asian Brazilians. On average, Asian Brazilians with a university education had a cognitive orientation towards politics score 17% higher than Asian Brazilians without a university education, though we do not find a similar effect for institutional confidence. Overall, we find that ethnic identity, particularly for Asians, does not have a strong effect on either of the axes but education has different effects on them between different ethnic groups.